Association between Myopia and Glaucoma; A Cross-sectional Study: Association between Myopia and Glaucoma - Jabbar, Maryam; Fatima, Naseer; Siddique, Muhammad; Rashid, Faisal; Qureshi, Faryal; Mateen Bodla, Abdul (Pakistan Journal of Health Sciences, 2023)
Myopia is a major cause of worldwide avoidable blindness and its prevalence increasing rapidly. Objective: To investigate the prevalence of glaucomatous optic nerve damage with various myopia levels as well as the relationship between myopia and glaucoma. Methods: A multi-centered cross-sectional study was conducted from January 2022 to July 2022. 250 individuals between the ages of 40 and 65 were recruited using non-probability purposive sampling technique. Mild, moderate and severe degree of myopia who had never had any surgery were included. All subjects underwent refraction and the optic disc ratio was assessed by slit lamp biomicroscopy, perimetry was performed to evaluate the visual field defects and IOP was determined using air puff tonometer. Frequency of glaucoma indicated by presence of visual field defects, glaucomatous optic disc. SPSS software was used for data analysis. Results: 145 (58%) of the 250 total subjects were female and 105(42%) were male. 67 (26.8%) people had refractive errors of mild myopia up to 3D. While 85 (34%) had a severe degree of myopia (refractive error greater than 6D) and 98 (39.2%) had a moderate degree. No intragroup's intraocular pressure showed a significantly distinct configuration. Age-related VF anomalies (a larger blind region, a vertical cup to disc ratio, and an unjustified defect) were associated with both glaucoma and high myopia. Findings from the study indicated that glaucoma risk increased for those with high myopia (p=0.001). Conclusion: High myopia is strongly associated with glaucomatous changes and a high prevalence of optic disc damage.